Pendampingan Baca Tulis Al-Qur’an Pada Anak Usia Dini di Desa Kotah Jrengik Sampang - Takwallo (PT. ALHAFI BERKAH INDONESIA, 2023)
In Kotah village itself there are several places to recite the Koran, one of which is TPA al-Mas'udiyah. The author chose Sukamulya TPA because there are approximately 40 students, but there are only 2 ustadz and ustadzah teachers (tPA managers). Apart from that, the students' interest in studying the Koran varies, some are enthusiastic and serious, but there are also those who seem forced and lazy. Of course, as a first step, efforts that can be made to overcome this problem are to educate and instill in children from an early age a strong love for the Al-Qur'an. The author focuses on the problem formulation in this activity as: